Local Wisdom and the Effectiveness of Disaster Resilient Village Policy in West Bandung Regency - Rozie, Azharisman; Sulistiyo, Heru (MUHARRIK: Jurnal Dakwah dan Sosial, 2024)
This study aims to evaluate the effectiveness of the implementation of the Disaster Resilient Village policy based on local wisdom in West Bandung Regency, particularly in addressing the threat of earthquakes and landslides caused by the Lembang Fault, which stretches across densely populated areas. Using descriptive-qualitative research methods, this study analyzes the Disaster Resilient Village  program implementation process, the challenges faced, and the potential for integrating local Sundanese wisdom into disaster mitigation efforts. Data were collected through field observations, interviews with informants, and a review of Disaster Resilient Village  program documents in villages affected by the Lembang Fault. The results indicate that Disaster Resilient Village  implementation has had a positive impact through increased community capacity, disaster simulations, the development of evacuation routes, and the formation of disaster preparedness groups. However, the policy's effectiveness is hampered by several key factors, including suboptimal communication between institutions, outreach that has not specifically targeted areas vulnerable to the Lembang Fault, and a high dependence on Village Funds or external assistance, which hampers the program's sustainability. Furthermore, the study identified that the local wisdom of the Sundanese people—such as knowledge of natural signs, traditional earthquake-responsive construction practices, experience-based land use planning, and the transmission of values ​​through oral tradition—has not been fully integrated into formal disaster mitigation policies. This study concludes that the effectiveness of Disaster Resilient Village  in West Bandung Regency will increase through strengthening the organizational structure, formalizing local wisdom in village disaster planning documents, and increasing human resource capacity through training and academic support.